Electrostatic capillary collector for in-situ spectroscopic analysis of aerosols. Issue 6 (3rd June 2019) - Mahamuni, Gaurav; Ockerman, Byron; Novosselov, Igor
Abstract: Identification of particulate matter is important in assessing an individual's exposure to potentially harmful particles, such as aeroallergens, toxins, and emissions from combustion sources, which can contribute to cardio-pulmonary diseases. Efficient collection of aerosols is essential for aerosol exposure studies such as analysis of chemical and biological components. We present the design and evaluation of a capillary collector that collects PM2.5 onto the outer surface of a capillary for in-situ spectroscopic analysis. The capillary collector uses a needle-to-ring corona generator to charge particles; the electric field between a cylinder and a wire inserted into the bore of a capillary is used to collect the charged particles. Corona and repelling voltages are optimized for maximum collection of ambient PM2.5 particles and fluorescent polystyrene latex microspheres in the PM2.5 size range, on the capillary. The capillary collection efficiency of ambient PM2.5 at 3 slpm operating flow rate and optimal operating voltages is 63%. Fluorescence spectroscopy is used to quantify the collection of polystyrene latex microspheres. The fluorescence-based capillary collection efficiency is in close agreement with the capillary collection efficiency of ambient PM2.5 . The collection and analysis methodology can be used to develop a compact, low-cost sensor for in-situ spectroscopic analysis of aerosols to determine their chemical composition for source apportionment. Copyright © 2019 American Association for Aerosol Research